PPO.13 Does specialist antenatal care for women at risk of preterm birth affect patient selection, rate and outcomes of cervical cerclage?. (9th June 2014) - Burul, G; James, CP; Forya, F; Casagrandi, D; Tetteh, A; Al-Fahdi, B; Fox, G; Warner, D; Kenyon, A; David, AL
Abstract : Background: Evidence suggests that cervical cerclage should be offered to women after three or more previous preterm births (PTB) or second-trimester losses. Ultrasound-indicated cerclage reduces the rate of recurrent PTB in women with previous PTB or late miscarriage and a shortening cervix before 24 weeks. Patient selection is therefore critical for this intervention. Aim: To assess the impact of a specialist antenatal service for women at risk of PTB on patient selection for cervical cerclage, cerclage rates and pregnancy outcome after surgery. Methods: Women undergoing cervical cerclage were identified from the prospectively collected Anaesthetic Obstetric Procedure database and the PTB clinic database at University College London Hospital. Data on cervical cerclage and pregnancy outcomes were collected. Results: There were 210 cases of cerclage; 85 cases before the PTB clinic was established (January 2005–December 2008), and 125 cases since (January 2009–December 2012). The rate of cerclage per 1000 women delivered fell from 6 to 5. Median gestational age at cerclage placement fell after establishment of the clinic (17+0/40, 13+2–23+3 to 15+2/40, 12+2–23+4 weeks). The proportion of rescue cerclages fell (26% to 12%) and the proportion of elective cerclages (history-indicated) doubled (44% to 88%). The median GA at delivery increased from 28+2/40 (17+0–39+5) to 35+2/40 (18+0–41+5). Conclusion: The introduction of a specialist antenatal service for women at risk of PTB results in better patient selection for cerclage, earlier placement of cerclage, a reduction in rescue cerclages, and a lower rate of PTB and late miscarriage in those women who undergo surgery.